In Vitro Selection In Wheat To Recover Mutants Which Overproduce Lysine And Threonine - Abdul Kadir, Midhzar (1991)
Lysine and threonine cause feedback inhibition to aspartokinase, dihydropicolinate synthase, and homoserine dehydrogenase which result in growth inhibition due to lack of methionine. This research was conducted to study the effect of lysine, threonine and methionine on wheat seed development and amino acid content. Wheat spikes were grown in liquid media with three different concentrations of lysine, threonine or methionine. Concentrations used were 1 mM lysine and threonine (L T) , 1 mM lysine, threonine and methionine (LT M) and without lysine, threonine or methionine (0 L TM) . Spikes were cultured from anthesis for a period of 6 wk. Seed number per spike, seed weight and amino acid composition were analyzed. No significant effects on seed number per spike and seed weight were observed for spikes cultured in 1 mM L T medium. Spikes cultured in 1 m M L T medium had a significant reduction in. total concentration of ten amino acids. The reductions in the 1 0 amino acids lead to a significant 13% reduction in protein percentage. Inclusion of methionine with lysine and threonine overcame the inhibitory effect of lysine and threonine on accumulation of 7 amino acids. Addition of lysine, threonine and methionine also enhanced grain development by increasing seed number per spike. Inclusion of methionine does not overcome the significant reduction in total alanine, glutamate and glycine. It did improve the concentration of cysteine, isoleucine and valine when compared to the control.